(3eSGFd aj GdYjfs ((3Ydi GdMdHi Hf UGdM GdeQfOi s)
(3ChdgG (B:s
(3fHJOF HYhf Gddg hMSf Jhajbg afcJH cJGHkG fPcQ ajg eSGFd ai GdYjf eY LhGHgG eTQhMI edNUI eHQgfI s
(3BNQgG (B:s
(3hYOO LejY gPg GdeSGFd GdJi ai gPG GdcJGH eGFJG eSCdI hSHY eSGFd , haQZJ efgG s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B171 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs